Physical activity and sitting time patterns and sociodemographic correlates among 155,790 south american adults - Werneck, André O. (2023)
Fil: Werneck, André O. Universidade de São Paulo. Center for Epidemiological Research in Nutrition and Health. School of Public Health. Department of Nutrition; Brasil